Updated Distributional Records of Selected Kentucky Fishes - David J Eisenhour; Matthew R Thomas; J. Jacob Culp; Michael C Compton; Stephanie L Brandt; Rodney Pierce (Southeastern Fishes Council Proceedings, 2018)
Distribution records for 15 fish species of conservation interest are included for Kentucky. Notropis dorsalis, previously undocumented in Kentucky, is reported for the first time (Mayfield Creek drainage). Also reported are state rediscoveries of three species thought to be extirpated from Kentucky: Ichthyomyzon gagei (Tennessee River drainage), Hemitremia flammea (Lower Cumberland and Green river drainages), and Hybopsis amnis (upper Cumberland River drainage). Unreported drainage records comprise nine species: Ichthyomyzon castaneus (Salt River drainage and Upper Green River drainage); Ichthyomyzon unicuspis (Salt River drainage and upper Big Sandy River drainage); Campostoma pullum (Tennessee River drainage); Umbra limi (Obion Creek drainage); Lepomis marginatus (Blood River system); Ammocrypta pellucida (Tygart’s Creek drainage); Nothonotus camurus (Kinniconick Creek drainage); Percina sciera (Salt River drainage); and Percina squamata (Laurel River system). Finally, we report range extensions of Notropis maculatus (Mayfield Creek drainage and Clarks River system) and Typhlichthys subterraneus (Cumberland River drainage). All but four species (I. unicuspis, C. pullum, N. camurus, and P. sciera) have a state conservation status designation because they are rare or have limited (e.g., peripheral) distributions in Kentucky.
Keywords: Kentucky; range extension; distribution